2022
DOI: 10.1186/s13567-022-01097-y
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa biofilm dispersion by the mouse antimicrobial peptide CRAMP

Abstract: Pseudomonas aeruginosa (P. aeruginosa) is a known bacterium that produces biofilms and causes severe infection. Furthermore, P. aeruginosa biofilms are extremely difficult to eradicate, leading to the development of chronic and antibiotic-resistant infections. Our previous study showed that a cathelicidin-related antimicrobial peptide (CRAMP) inhibits the formation of P. aeruginosa biofilms and markedly reduces the biomass of preformed biofilms, while the mechanism of eradicating bacterial biofilms remains elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…The higher MICs for biofilm-embedded bacteria also suggest that treatment with neomycin, polymyxin B, gentamicin, or enrofloxacin may be less effective in treating chronic otitis caused by P. aeruginosa . Thereby, dogs can serve as a model for human infections; by studying P. aeruginosa biofilms in dogs, researchers can gain a better understanding of how these structures contribute to infection and develop more effective treatments [ 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher MICs for biofilm-embedded bacteria also suggest that treatment with neomycin, polymyxin B, gentamicin, or enrofloxacin may be less effective in treating chronic otitis caused by P. aeruginosa . Thereby, dogs can serve as a model for human infections; by studying P. aeruginosa biofilms in dogs, researchers can gain a better understanding of how these structures contribute to infection and develop more effective treatments [ 68 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stably infected Caco-2 intestinal cells expressing HBD-2 and HBD-3 showed antibiofilm activity against P. aeruginosa, indicating that therapeutic strategies that enhance endogenous cellular AMP production might be successful as antibiofilm therapy [56]. The treatment of P. aeruginosa with CRAMP led to the dispersion of established biofilms by affecting exopolysaccharides, as well as promoting the flagellar motility of the bacteria inside the biofilm [57]. Yasir et al generated melimine, a chimeric AMP from melittin and protamine, which inhibited biofilm formation by >75% at one-fold MIC by depolarizing the cell membranes of biofilm cells.…”
Section: Enterococcus Faecalismentioning
confidence: 99%
“…Our previous studies have shown that the murine antimicrobial peptide (AMP) CRAMP-34 inhibits bio lm formation and eradicates the mature bio lms of the bio lm model strain Pseudomonas aeruginosa PAO1 [19,20]. However, whether CRAMP-34 has the same inhibitory effect on E. coli bio lms is yet to be clari ed.…”
Section: Introductionmentioning
confidence: 99%